2013
DOI: 10.1073/pnas.1219221110
|View full text |Cite
|
Sign up to set email alerts
|

Interferon regulatory factor 3 controls interleukin-17 expression in CD8 T lymphocytes

Abstract: IFN regulatory factor (IRF) 3 plays a key role in innate responses against viruses. Herein we assessed its contribution to T-cell activation. We observed that poly(I:C)-induced IRF3 activation in CD8 T cells represses IL-17 expression in a type I IFN-independent fashion. Even in the absence of poly(I:C), polyclonally activated naïve IRF3−/− CD8 T cells expressed high levels of IL-17 and IL-23Rin comparison with wild-type cells. Furthermore, IRF3 −/− OT1 cells adoptively transferred into wild-type hosts also pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 31 publications
2
27
0
1
Order By: Relevance
“…In this study, we found that human CAR T cells can produce significant levels of IFNβ, thereby supplying their own ‘Signal 3’. The ability of T cells to produce IFNβ was previously reported in mouse CD8 T cells only (Ysebrant de Lendonck et al, 2013). We show here that optimal augmentation of CD3ζ, CD28 and 4-1BB signaling in 1928z-41BBL T cells results in a durable activation of IRF7/IFNβ signal pathway, especially in CD4 T cells.…”
Section: Discussionmentioning
confidence: 82%
“…In this study, we found that human CAR T cells can produce significant levels of IFNβ, thereby supplying their own ‘Signal 3’. The ability of T cells to produce IFNβ was previously reported in mouse CD8 T cells only (Ysebrant de Lendonck et al, 2013). We show here that optimal augmentation of CD3ζ, CD28 and 4-1BB signaling in 1928z-41BBL T cells results in a durable activation of IRF7/IFNβ signal pathway, especially in CD4 T cells.…”
Section: Discussionmentioning
confidence: 82%
“…The transcription factor Eomesodermin (Eomes) is associated with cytolytic T cell differentiation (46), T-bet is associated with IFN-γ from T cells (47), and ROR-γT with IL-17 from T cells (48). A more recent paper showed that IRF3 is activated during responses of purified naïve T cell to anti-CD3/anti-CD28 (12). Moreover, CD4 and CD8 T cells that were differentiated under Th17 and Tc17 conditions express ROR-γt and activated IRF3 together and both of these transcription factors interacted together in the cytoplasm of responding T cells (12).…”
Section: Discussionmentioning
confidence: 99%
“…A more recent paper showed that IRF3 is activated during responses of purified naïve T cell to anti-CD3/anti-CD28 (12). Moreover, CD4 and CD8 T cells that were differentiated under Th17 and Tc17 conditions express ROR-γt and activated IRF3 together and both of these transcription factors interacted together in the cytoplasm of responding T cells (12). Binding of IRF3 to ROR-γt intracellularly in Tc17 cell dampened IL-17 production from responding Tc17 cells but not from responding naïve T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, IL-15 production by inflammatory monocytes is required to promote memory cytolytic CD8 T cells against Listeria infection [17]. In one study, the impact of IRF3 on T cell function was examined in CD8 cells, but this was limited to the context of poly I:C induced activation [21]. While these studies collectively suggest that IRF3 is important for antiviral T cell responses, the role of IRF3 in promoting effector and memory T cell responses during virus infection has not been directly addressed.…”
Section: Introductionmentioning
confidence: 99%